Phase-lead Repetitive Control of a PMSM with Field-oriented Feedback Linearization and a disturbance observer - Zheng, Yusai; Cao, Zhenwei; Man, Zhihong; Kumar, Artheec; Wang, Song (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
The permanent magnetic synchronous motors (PMSMs) are nonlinear and subject to different kinds of uncertainties, which brings challenges to design a controller for the robustness and accurate tracking. This paper presents a phase-lead repetitive control (PLRC) with field-oriented feedback linearization and a disturbance observer to improve the robustness and the speed tracking for a PMSM system. Firstly, feedback linearization is designed to cancel the nonlinearity in the field-oriented based PMSM model, in which the field-oriented control (FOC) decouples the magnetic loop and the torque loop in the PMSM system to simplify the PMSM control design. Secondly, the PLRC is designed to decrease the speed fluctuations caused by the external periodic disturbance, while the disturbance observer (DO) is employed to estimate and compensate the non-periodic uncertainties including the payload. Finally, the proposed control is validated by numerical simulations. The results show the proposed control has a superior speed tracking performance than its counterparts.